Problems Regarding the Impact of Residential Land Acquisition on Land and Building Compensation Does Not Cover Community Business Activities - Mansyah, Angra; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine how the problems, laws, and obstacles of the impact of land acquisition for settlements on land and building compensation do not cover community business activities, a case study of the Kendari-Toronipa road, the author uses the method of legal research is empirical legal research (sociological). Namely research that uses empirical facts taken from human behavior, both verbal behavior obtained through interviews and real behavior carried out through direct observation with normative juridical as a writing approach, The results of the study show that the construction of the Kendari-Toronipa main road has reaped many problems including compensation that is not in accordance with the initial agreement or changes from the relevant government to the affected community, then there is no compensation for community business activities, this shows the community's ignorance and the absence of socialization regarding compensation for land does not cover business activities. The draft planning and legal certainty applicable in terms of land acquisition and compensation in Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest and its update to the Government Regulation in Lieu of Law Number 39 of 2023. The Southeast Sulawesi Provincial Government in the construction of the Kendari-Toronipa road which is based on Land Acquisition for Development in the Public Interest, however, in its implementation not all are applied from the informants interviewed by the researcher, many of them still receive compensation that is not in accordance with the agreement or deliberation that has been carried out, and the application of compensation does not cover community business activities that are not applied at all by the government, in this case in the case of compensation for Kasilampe Beach, Mata Village, and businesses that do not receive compensation for the business losses they experience.Keywords: compensation; land acquisition; Problems.